(untitled) (Journal of Asian Development Studies, 2026)
This paper examines entrepreneurial intention (EI) among university students as an outcome of AIL, in relation to both the direct effect of AI literacy (AIL) as well as indirect influence via three cognitive-behavioural processes, namely AI-specific entrepreneurial self-efficacy (ESE), AI-enabled opportunity recognition (OR) and pragmatic thinking (PT). The model integrates the Theory of Planned Behaviour (TPB) and Social Cognitive Theory (SCT). A quantitative survey questionnaire was distributed to students at four universities (two public and two private), and 460 valid responses were collected from users of AI-enabled tools and platforms. Measurement and structural models were evaluated to test parallel mediation processes from AIL to EI via three mediators, and data were analysed using PLS-SEM. Results indicate a positive, statistically significant direct relationship between AIL and EI. In contrast, the indirect effects of AI in AI-specific ESE, AI-enabled OR, and PT are not statistically significant, which suggests that these processes have not yet developed strong mediating relationships between AIL and EI in the population sampled in the present study. Thus, AI-literate students tend to turn their AI knowledge and capabilities directly into EI instead of following the examined cognitive and behavioural routes. The study is limited by its cross-sectional study design and single-country context (Pakistan), which may limit generalizability. There is a need for future research to better understand mediators and boundary conditions. Educators and university administrations ought to create entrepreneurship programs that will enhance AIL and intentionally establish AI-ESE, OR, and PT, supported by hands-on learning experiences in which students use AI tools to solve problems in new venture creation. This research builds on AIL-EI literature by proposing a TPB-SCT-based parallel mediation model with limited mediation in an AI-intensive higher education setting and by promoting an agenda to address the link between AIL and EB in resource-constrained settings